Social Awareness and Ideology: Self-Assessment and Socio-Civic Knowledge Competence - Maderick, Joseph; Grubaugh , Steven; Levitt, Gregg; Deever, Allen (Technium Social Sciences Journal, 2021)
"The fundamental cause of the trouble is that in the modern world the stupid are cocksure while the intelligent are full of doubt" (Russell, 1933, p. 28). One seldom hears doubt in the espousing of socio-civic, cultural, or political pronouncements. While the voices seem to always be “cocksure;” we first ask at what level is their objective knowledge and how well do they self-assess that knowledge? We explore how ideological positioning is related to self-assessment and objective knowledge. We conducted a non-comparative (absolute) quantitative study through an email survey of 330 residents of the U.S. over the age of 18 that examined objective socio-civic knowledge and self-assessed ideology and wokeness. The experimental results confirmed misestimations consistent with Dunning-Kruger Effects.